Australia : Financial Sector Assessment Program-Technical Note-Bank Resolution and Crisis Management. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note analyzes the existing legal and institutional frameworks in Australia, including coordination arrangements and focuses on crisis preparedness, including recovery and resolution planning as well as the Reserve Bank of Australia's (RBA) lender-of-last resort functions. The analysis highlights that Australia has a well-established framework for financial stability, surveillance and policy formulation and the resolution regime for financial institutions has been significantly enhanced since the financial crisis. Australian Prudential Regulation Authority (APRA) has made progress in developing recovery planning requirements for the banking industry, extending these from large to medium sized and smaller banks. However, there is a need to better integrate the recovery planning within the risk management framework and operational testing exercises and to significantly enhance APRA's work on resolution planning, particularly for the largest banks. The paper recommends that the Australian authorities should introduce an ex-ante funded deposit insurance scheme, based on best international practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet